Student Academic Procrastination That Boils Down to Gadget Addiction: Post-Pandemic Challenges to Solve - Sri Wahyuni; Rosnila Hura; Herbin Simanjuntak; Muliani Zendrato; Vernando Purba; Meri KD Sitepu (LP. Ma'arif Janggan Magetan, 2022)
The prolonged pandemic conditions experienced by the world forced changes in various aspects of life and unwittingly formed a new